Intravenous thrombolysis for acute ischemic stroke in centenarians - Baena Álvarez, B.; García-Madrona, S.; Sainz Amo, R.; Rodríguez Jorge, F.; Gómez Corral, J.; Vera Lechuga, R.; Matute Lozano, M. C.; Sánchez Sánchez, A.; De Felipe Mimbrera, A.; Cruz Culebras, A.; Masjuan Vallejo, J. (European geriatric medicine, 2021)
Key summary points Aim Evaluate clinical and functional outcomes of centenarians treated with intravenous thrombolysis for acute ischemic stroke. Findings Three out of four patients were functionally independent 90 days after discharge. No serious hemorrhagic or systemic adverse events secondary to treatment were registered.. Message Intravenous thrombolysis may be beneficial in patients over 100 years. Purpose The benefit of intravenous alteplase is well established for patients with disabling stroke symptoms regardless of age, although data on outcomes in centenarian patients are scarce. We present our experience in patients beyond 100 years. Methods Descriptive study including centenarians from our single-centre prospective registry who underwent intravenous thrombolysis with alteplase for acute ischemic stroke in our tertiary university hospital. Clinical variables and functional outcome at 3 months were collected. Results Four patients, all women, functionally independent (mRS ≤ 2) were included. Treatment with alteplase was applied within 4.5 h of stroke onset. One patient complicated with pneumonia and died. Two patients were functionally independent (mRS ≤ 2) at discharge, while the third was partially dependent (mRS of 3 at discharge), improving after 3 months, (mRS 2). No serious hemorrhagic or systemic adverse events were registered. Conclusion In our experience, intravenous thrombolysis may be beneficial and should be considered in patients over 100 years old with no previous disability.